Peran Budaya Organisasi terhadap Kesiapan Karyawan dalam Menghadapi Perubahan Organisasi pada PT Gojek Indonesia - Rachmadina, Syahira; Pramesdianti , Najla Putri; Amrina, Wafiyati Nur; Agustiani , Dewi Resti; Nurasiah , Sofa Farihah (PENG: Jurnal Ekonomi dan Manajemen, 2026)
This study examines the role of organizational culture in employees’ readiness to face organizational change at PT Gojek Indonesia. The researcher employed a qualitative approach using descriptive methods, conducting an interview with one of PT Gojek Indonesia’s employees to gather supporting data. The interview results indicate that the culture at PT Gojek Indonesia is characterized by an open work environment that encourages discussion, professional yet relaxed communication, the use of technology in daily work activities, and excellent teamwork. This culture fosters a collaborative and adaptive work environment that supports the organizational change process. Furthermore, employees demonstrate a strong readiness to embrace change. This readiness indicates that PT Gojek Indonesia plays a positive role in fostering employees’ readiness to face change. .